Positive photosensitive resin composition and display element using the same
By using a positive photosensitive resin composition including a siloxane-based copolymer, a 1,2-quinonediazide compound and a specific UV absorber, the problems of insufficient sensitivity, low resolution and insufficient weatherability in the OLED display device in the prior art are solved, and high resolution pattern formation and panel reliability are improved.
Patent Information
- Application Number
- CN202080071401.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-11
- Filing Date
- 2020-10-08
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2040-10-08
AI Technical Summary
The conventional photosensitive resin compositions are insufficient in OLED display devices, have low resolution and are not easily dissolved, resulting in developing residues and pattern defects, and have insufficient weather resistance, which affects the reliability of the display element.
The insulating, heat resistance and solubility of the resin are improved by minimizing the content of unreacted monomers and catalysts.
High resolution pattern formation in OLED display devices is realized, reducing development residues and pattern defects, and improving the reliability and weather resistance of the panel.
Smart Images

Figure CN114556216B_ABST
Abstract
Description
Technical Field
[0001] Cross-references to related applications
[0002] This application claims the benefit of Korean Patent Application No. 10-2019-0126256, filed on October 11, 2019, the entire contents of which are incorporated herein by reference.
[0003] The present invention relates to a positive photosensitive resin composition. More specifically, the present invention relates to a positive photosensitive resin composition that can achieve insulation and heat resistance and high resolution of an organic light emitting diode (hereinafter referred to as OLED) display device, can form an environmentally resistant pattern due to excellent light resistance and heat resistance, and can reduce pattern defects caused by development residues that may be generated during development or the difference in solubility generated at the boundary between exposed and non-exposed parts. Background Art
[0004] In recent years, the display industry is developing OLED devices, which display images through self-luminous layers in a liquid crystal display device (hereinafter referred to as LCD) that displays images through an independent light source such as a backlight unit (hereinafter referred to as BLU), and do not have a BLU. In particular, the OLED display device is in a trend of being applied to small electronic devices such as smartphones and large electronic devices such as televisions. In addition, the OLED display device can make the panel on which the organic light-emitting layer is deposited into a flexible panel, so that the display device can be bent, and can be applied to various forms of display devices such as outdoor advertising or automobiles.
[0005] The OLED display includes a pixel defining layer (PDL) layer that divides the boundaries between self-luminous red, green, and blue pixels and insulates them, and an interlayer insulating film having both insulating properties and electrode flatness properties under the PDL layer. At this time, the PDL layer is precisely patterned by a photoetching process, so a photosensitive resin composition containing a polyamic acid compound has been widely used as a material for forming the PDL layer.
[0006] However, compared with the photosensitive resin composition containing siloxane resin, the photosensitive resin composition containing the polyamic acid and polyimide is generally not sensitive enough and has a high film thickness change rate in the process, so the productivity is low. Since the main function of the PDL layer is to uniformly form red, green, and blue pixels of different sizes (i.e., resolution) is insufficient, the quality of the final display element panel may be affected. In addition, the insoluble characteristics of the polyimide resin may cause the development residue generated during development.
[0007] Furthermore, for OLED display element panels, as displays exposed to sunlight or various weather conditions (such as large advertisements or automobiles) become more popular, there is a need to develop display elements with improved weatherability. Summary of the invention
[0008] Technical issues
[0009] In order to solve the problems of the prior art as described above, the present invention provides a positive photosensitive resin composition, a pattern forming method for a display element using the composition, and a positive photosensitive siloxane resin composition, which not only have excellent properties such as sensitivity, resolution and flatness, but also have excellent weather resistance, thereby ensuring excellent panel reliability, and can be effectively applied to interlayer insulating films, planarizing films or PDLs in various OLED displays.
[0010] Problem Solving Solutions
[0011] The present invention provides a positive photosensitive resin composition, characterized in that the positive photosensitive resin composition comprises:
[0012] a) Siloxane copolymers;
[0013] b) 1,2-quinonediazide compounds;
[0014] c) one or more UV absorbers represented by the following Chemical Formula 1; and
[0015] d) a solvent,
[0016] [Chemical formula 1]
[0017]
[0018] In the chemical formula 1,
[0019] R1 is selected from hydrogen, substituted or unsubstituted C1-20 alkyl, substituted or unsubstituted C3-20 cycloalkyl, substituted or unsubstituted C2-10 alkenyl, substituted or unsubstituted C6-18 aryl, substituted or unsubstituted C7-18 alkaryl, substituted or unsubstituted C7-18 aralkyl, substituted or unsubstituted C1-20 alkoxy, substituted or unsubstituted C1-30 acetal, substituted or unsubstituted C1-30 a substituted or unsubstituted C1-20 heteroalkyl group, a substituted or unsubstituted C3-20 heterocycloalkyl group, a substituted or unsubstituted C2-10 heteroalkenyl group, a substituted or unsubstituted C6-18 heteroaryl group, a substituted or unsubstituted C7-18 heteroalkylaryl group, a substituted or unsubstituted C7-18 heteroaralkyl group, a substituted or unsubstituted C1-20 heteroalkoxy group, a substituted or unsubstituted C1-30 heteroacetal group (hetero acetal) group and a substituted or unsubstituted C1-30 heterohemiacetal group (hetero hemiacetal) group,
[0020] R2 to R5 are each independently the same or different and are selected from hydrogen, hydroxy, substituted or unsubstituted C1-20 alkyl, substituted or unsubstituted C3-20 cycloalkyl, substituted or unsubstituted C2-10 alkenyl, substituted or unsubstituted C6-18 aryl, substituted or unsubstituted C7-18 alkaryl, substituted or unsubstituted C7-18 aralkyl, substituted or unsubstituted C1-20 alkoxy, substituted or unsubstituted C1-30 acetal, substituted or unsubstituted C1-30 The functional group is a hemiacetal group, a substituted or unsubstituted C1-20 heteroalkyl group, a substituted or unsubstituted C3-20 heterocycloalkyl group, a substituted or unsubstituted C2-10 heteroalkenyl group, a substituted or unsubstituted C6-18 heteroaryl group, a substituted or unsubstituted C7-18 heteroalkylaryl group, a substituted or unsubstituted C7-18 heteroaralkyl group, a substituted or unsubstituted C1-20 heteroalkoxy group, a substituted or unsubstituted C1-30 heteroacetal group and a substituted or unsubstituted C1-30 heterohemiacetal group.
[0021] According to another embodiment of the present invention, there is provided a cured film including a cured product of the positive photosensitive resin composition.
[0022] According to yet another embodiment of the present invention, a display element is provided, comprising a cured product of the positive photosensitive resin composition.
[0023] According to the positive photosensitive resin composition containing a siloxane copolymer of the present invention, the unreacted monomer and catalyst content are reduced to the maximum extent, and a UV absorber with a specific structure is used so as to be able to show the characteristics of siloxane, such as excellent insulation, heat resistance that can maintain a stable form up to about 350°C, low moisture absorption rate that is not easy to absorb moisture, etc. Therefore, the present invention can provide a PDL layer that divides and insulates the boundaries between pixels of a display element such as an OLED, and an interlayer insulating film that has both insulation characteristics and electrode flatness characteristics at the bottom of the PDL layer, thereby significantly reducing the defect rate caused by moisture that affects the operational reliability of the OLED panel. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of a pattern substrate used to evaluate the reliability of OLED for each embodiment and comparative example. DETAILED DESCRIPTION
[0025] In the following, the present invention will be described in more detail. The terms and words used in this specification and claims should not be interpreted as being limited to typical meanings or dictionary definitions, and should be interpreted as having meanings and concepts that are consistent with the technical ideas of the present invention, on the principle that the inventor can appropriately define the concepts of the terms to describe the invention in the best way.
[0026] In addition, the word "comprising" used in the description of the present invention specifically refers to a certain characteristic, field, integer, step, operation, element and / or component, and does not exclude the existence or addition of other characteristics, fields, integers, steps, operations, elements and / or components.
[0027] According to one embodiment of the present invention, there may be provided a positive photosensitive resin composition including: a) a siloxane-based copolymer; b) a 1,2-quinonediazide compound; c) one or more UV absorbers represented by the following Chemical Formula 1; and d) a solvent.
[0028] [Chemical formula 1]
[0029]
[0030] In the chemical formula 1,
[0031] R1 is selected from hydrogen, substituted or unsubstituted C1-20 alkyl, substituted or unsubstituted C3-20 cycloalkyl, substituted or unsubstituted C2-10 alkenyl, substituted or unsubstituted C6-18 aryl, substituted or unsubstituted C7-18 alkaryl, substituted or unsubstituted C7-18 aralkyl, substituted or unsubstituted C1-20 alkoxy, substituted or unsubstituted C1-30 acetal, substituted or unsubstituted C1-30 hemiacetal ), a substituted or unsubstituted C1-20 heteroalkyl, a substituted or unsubstituted C3-20 heterocycloalkyl, a substituted or unsubstituted C2-10 heteroalkenyl, a substituted or unsubstituted C6-18 heteroaryl, a substituted or unsubstituted C7-18 heteroalkylaryl, a substituted or unsubstituted C7-18 heteroaralkyl, a substituted or unsubstituted C1-20 heteroalkoxy, a substituted or unsubstituted C1-30 heteroacetal and a substituted or unsubstituted C1-30 heterohemiacetal,
[0032] R2 to R5 are each independently the same or different and are selected from hydrogen, hydroxy, substituted or unsubstituted C1-20 alkyl, substituted or unsubstituted C3-20 cycloalkyl, substituted or unsubstituted C2-10 alkenyl, substituted or unsubstituted C6-18 aryl, substituted or unsubstituted C7-18 alkaryl, substituted or unsubstituted C7-18 aralkyl, substituted or unsubstituted C1-20 alkoxy, substituted or unsubstituted C1-30 acetal, substituted or unsubstituted C1-30 The functional group is a hemiacetal group, a substituted or unsubstituted C1-20 heteroalkyl group, a substituted or unsubstituted C3-20 heterocycloalkyl group, a substituted or unsubstituted C2-10 heteroalkenyl group, a substituted or unsubstituted C6-18 heteroaryl group, a substituted or unsubstituted C7-18 heteroalkylaryl group, a substituted or unsubstituted C7-18 heteroaralkyl group, a substituted or unsubstituted C1-20 heteroalkoxy group, a substituted or unsubstituted C1-30 heteroacetal group and a substituted or unsubstituted C1-30 heterohemiacetal group.
[0033] The positive photosensitive resin composition of the present invention contains one or more phenolic hydroxyl groups and a UV absorber having an alkoxy group, which is different from the conventional benzotriazole-based cross-linkable reaction, thereby ensuring excellent panel reliability. It not only has excellent performance such as sensitivity, resolution, and flatness, but also has excellent weather resistance and excellent ultraviolet absorption rate.
[0034] In addition, the positive photosensitive siloxane composition of the present invention includes a siloxane resin for forming an insulating film that can achieve insulation and heat resistance and high resolution of an organic light emitting diode (hereinafter referred to as OLED) display device.
[0035] More specifically, the photosensitive resin composition according to the present invention can utilize a siloxane copolymer of two reactive silane compounds of a specific structure that minimizes residual impurities such as unreacted monomers and catalysts, and due to its excellent light resistance and heat resistance, can form a pattern with environmental resistance, and can also show the effect of reducing development residues that may be generated during development or pattern defects caused by the difference in solubility generated at the boundary between the exposed and non-exposed parts.
[0036] Furthermore, the present invention includes a cured product formed from the positive photosensitive resin composition and a display device having the cured product.
[0037] Hereinafter, the siloxane-based copolymer, the 1,2-quinonediazide compound, the UV absorber, and the solvent used in the positive photosensitive resin composition of the present invention will be described in detail in sequence.
[0038] a) Siloxane copolymers
[0039] The siloxane copolymer according to the present invention is used in a photosensitive resin composition, so that it not only has excellent properties such as sensitivity and resolution, but also maintains a low moisture absorption rate, which can help ensure excellent panel reliability.
[0040] Such a siloxane-based copolymer can be obtained as a polycondensate by hydrolyzing and polycondensing i) a silane compound represented by the following Chemical Formula 2 and ii) a silane compound represented by the following Chemical Formula 3, and removing impurities such as unreacted monomers and the like.
[0041] According to one embodiment, the siloxane-based copolymer may be obtained by hydrolyzing and polycondensing i) 10 to 90 parts by weight of a silane compound represented by the following Chemical Formula 2; and ii) 10 to 90 parts by weight of a silane compound represented by the following Chemical Formula 3 relative to 100 parts by weight of the entire monomer.
[0042] [Chemical formula 2]
[0043] (R6) n Si(R7) 4-n
[0044] In the chemical formula 2,
[0045] R6 may be the same or different from each other and is selected from a hydrogen atom, a C1-10 alkyl group, a C2-10 acyl group, a C2-10 alkenyl group or a C6-20 aryl group,
[0046] R7 may be the same or different from each other and is selected from a hydrogen atom, an alkoxy group or a chloro group,
[0047] n is an integer from 1 to 3,
[0048] [Chemical formula 3]
[0049] Si(OR8)4
[0050] In the chemical formula 3,
[0051] R8 are each independently the same or different and are selected from methyl, ethyl, propyl, isopropyl or butyl.
[0052] The silane compound represented by the chemical formula 2 as the reactive silane may be, for example, phenyltrimethoxysilane, diphenyldimethoxysilane, methyltrimethoxysilane, dimethyldiphenylsilane, 1-naphthyltrimethoxysilane, propyltrimethoxysilane, octyltrimethoxysilane, etc., which may be used alone or in combination of two or more.
[0053] The reactive silane represented by the chemical formula 2 may be used in an amount of 10 to 90 parts by weight relative to 100 parts by weight of the total monomers. If the content of the reactive silane compound of the chemical formula 2 is less than 10 parts by weight, cracks may occur when the cured product is formed, and if the content is greater than 90 parts by weight, pattern collapse may occur, making it difficult to achieve high resolution.
[0054] In addition, the compound represented by the chemical formula 3 used in the present invention as the tetrafunctional reactive silane may be, for example, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, etc., which may be used alone or in combination of two or more.
[0055] The reactive silane represented by the chemical formula 3 may be used in an amount of 10 to 90 parts by weight relative to 100 parts by weight of the total monomers. If the content of the reactive silane of the chemical formula 3 is less than 10 parts by weight, the speed of dissolving in the developer is very slow, which is not conducive to sensitivity. If the content is greater than 90 parts by weight, the solubility in the solvent used for the composition is low, and precipitation may occur.
[0056] The conditions for the hydrolysis and polycondensation reactions for preparing the siloxane copolymer are not greatly limited and can be carried out according to conditions known in the art. For example, the polymerization reaction can be carried out at a temperature of 50 to 100° C. for 4 to 24 hours. In addition, the reaction can be carried out under an inert environment.
[0057] In addition, during the hydrolysis and polycondensation, an acid catalyst or a base catalyst may also be used. The acid catalyst that can be used in the method may be hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, acetic acid, oxalic acid, formic acid, acetic acid, propionic acid, butyric acid, valeric acid, and the base catalyst may be sodium hydroxide, potassium hydroxide, ammonia and organic amine, alkyl ammonium hydroxide salt, which may be used alone or in combination of two or more and used simultaneously or in separate steps.
[0058] In addition, after the polycondensation reaction is completed, a step of removing unreacted monomers and catalysts through an extraction process with water and an organic solvent may be performed.
[0059] The siloxane copolymer provided by the method may include a copolymer having an unreacted monomer content of less than 10% by weight and a residual catalyst content of less than 2,000 ppm. For the siloxane copolymer from which the unreacted monomer and the catalyst are removed, the storage stability is improved, and the developing residue caused by the side reaction in the curing film process of the photosensitive resin composition is improved. At this time, if the catalyst content is greater than or equal to 2000 ppm, the excess catalyst causes the sensitivity to become slow, or corrosion of the lower or upper metal wiring due to diffusion may occur. Therefore, when using the siloxane copolymer, the desired effect can be achieved only if it is refined to a catalyst content within a specific range as used in the method of the present invention.
[0060] In addition, the polystyrene-equivalent weight average molecular weight (Mw) of the finally obtained siloxane copolymer may be 1,000 g / mol to 30,000 g / mol. The polystyrene-equivalent weight average molecular weight (Mw) may be measured by a standard analytical method using a gel permeation chromatography (GPC) system such as an e2695 Alliance Separation Module of Waters.
[0061] If the polystyrene-converted weight average molecular weight (Mw) of the siloxane copolymer is less than 1,000 g / mol, the residual film rate in the development process decreases or the heat resistance decreases in the evaluation of the positive photosensitive resin composition, and the moisture absorption rate is poor. In addition, if the converted weight average molecular weight (Mw) is greater than 30,000 g / mol, the sensitivity and developability of the positive photosensitive resin composition will decrease.
[0062] b) 1,2-quinonediazide compounds
[0063] According to the photosensitive resin composition containing 1,2-quinonediazide compound of the present invention, the exposed part thereof can be dissolved in alkaline developer and form a positive pattern which is removed by the developing process.
[0064] The 1,2-quinonediazide compound in the present invention has a structure in which a ballast having a phenolic hydroxyl group and naphthoquinonediazidesulfonic acid form an ester bond.
[0065] As the naphthoquinonediazidesulfonic acid, 4-naphthoquinonediazidesulfonyl halide or 5-naphthoquinonediazidesulfonyl halide can be used. The ester compound obtained from the 4-naphthoquinonediazidesulfonyl halide has absorption in the i-line (wavelength of 365nm) field, and is therefore suitable for i-line exposure. In addition, the ester compound obtained from the 5-naphthoquinonediazidesulfonyl halide has absorption in a wide range of wavelengths, and is therefore suitable for exposure under a wide range of wavelengths. Depending on the wavelength of exposure, a 4-naphthoquinonediazidesulfonic acid compound or a 5-naphthoquinonediazidesulfonic acid compound can be selected or a mixture of the two can be used.
[0066] In addition, the content of the 1,2-quinonediazide compound varies depending on the esterification rate of naphthoquinonediazidesulfonic acid or the physical properties of the siloxane copolymer used, the required sensitivity, and the optimal amount of contrast caused by the difference in solubility between the exposed part and the non-exposed part. Specifically, the 1,2-quinonediazide compound may include 5 to 50 parts by weight or 10 to 35 parts by weight relative to 100 parts by weight of the siloxane copolymer. When 5 to 50 parts by weight of the 1,2-quinonediazide compound is included in the photosensitive resin composition, the patterning characteristics become good due to the difference in solubility between the exposed and non-exposed parts.
[0067] At this time, if the content of the 1,2-quinonediazide compound is less than 5 parts by weight, the dissolution contrast between the exposed part and the non-exposed part decreases, and the photosensitive property is not obtained. On the other hand, if the amount of the 1,2-quinonediazide compound used is greater than or equal to 50 parts by weight, the compatibility decreases, causing white turbidity in the cured film, or the decomposition of the quinonediazide compound that may be generated during the thermal curing process causes the insulation property of the cured product to decrease, or the gas components of the decomposed product may cause problems in subsequent processes.
[0068] c) UV absorber
[0069] The composition of the present invention specifically includes a UV absorber represented by the following Chemical Formula 1.
[0070] [Chemical formula 1]
[0071]
[0072] In the chemical formula 1,
[0073] R1 is selected from hydrogen, substituted or unsubstituted C1-20 alkyl, substituted or unsubstituted C3-20 cycloalkyl, substituted or unsubstituted C2-10 alkenyl, substituted or unsubstituted C6-18 aryl, substituted or unsubstituted C7-18 alkaryl, substituted or unsubstituted C7-18 aralkyl, substituted or unsubstituted C1-20 alkoxy, substituted or unsubstituted C1-30 acetal, substituted or unsubstituted C1-30 hemiacetal, substituted or unsubstituted a substituted C1-20 heteroalkyl group, a substituted or unsubstituted C3-20 heterocycloalkyl group, a substituted or unsubstituted C2-10 heteroalkenyl group, a substituted or unsubstituted C6-18 heteroaryl group, a substituted or unsubstituted C7-18 heteroalkylaryl group, a substituted or unsubstituted C7-18 heteroaralkyl group, a substituted or unsubstituted C1-20 heteroalkoxy group, a substituted or unsubstituted C1-30 heteroacetal group, and a substituted or unsubstituted C1-30 heterohemiacetal group,
[0074] R2 to R5 are each independently the same or different and are selected from hydrogen, hydroxy, substituted or unsubstituted C1-20 alkyl, substituted or unsubstituted C3-20 cycloalkyl, substituted or unsubstituted C2-10 alkenyl, substituted or unsubstituted C6-18 aryl, substituted or unsubstituted C7-18 alkaryl, substituted or unsubstituted C7-18 aralkyl, substituted or unsubstituted C1-20 alkoxy, substituted or unsubstituted C1-30 acetal, substituted or unsubstituted C1-30 The functional group is a hemiacetal group, a substituted or unsubstituted C1-20 heteroalkyl group, a substituted or unsubstituted C3-20 heterocycloalkyl group, a substituted or unsubstituted C2-10 heteroalkenyl group, a substituted or unsubstituted C6-18 heteroaryl group, a substituted or unsubstituted C7-18 heteroalkylaryl group, a substituted or unsubstituted C7-18 heteroaralkyl group, a substituted or unsubstituted C1-20 heteroalkoxy group, a substituted or unsubstituted C1-30 heteroacetal group and a substituted or unsubstituted C1-30 heterohemiacetal group.
[0075] At this time, the functional groups of R1 to R5, namely, alkyl, cycloalkyl, alkenyl, aryl, alkaryl or aralkyl, may be substituted by a hydroxyl group, a halogen atom, a C1-12 alkyl group or an alkoxy group.
[0076] Furthermore, the functional groups of R1 to R5, ie, alkyl, cycloalkyl, alkenyl, aryl, alkaryl or aralkyl groups, may also be interrupted by oxygen atoms, sulfur atoms, carbonyl groups, ester groups, amide groups or imine groups.
[0077] In addition, the functional groups of R1 to R5 may be substituted and interrupted by the above-mentioned substituents in combination.
[0078] Preferably, in the present invention, the alkyl group may be a linear or branched alkyl group.
[0079] In the chemical formula 1, R1 may be a substituted or unsubstituted C1-20 alkyl group, R2 to R4 may each independently or simultaneously be a functional group selected from hydrogen and a substituted or unsubstituted C1-20 alkoxy group, and R5 may be a hydroxyl group.
[0080] In the chemical formula 1, R1 may be a functional group selected from a substituted or unsubstituted C1-20 alkyl group, a substituted or unsubstituted C1-30 acetal group, and a substituted or unsubstituted C1-30 hemiacetal group, and R2 to R5 may be a substituted or unsubstituted C1-20 alkyl group independently or simultaneously. The functional group of R1, i.e., the alkyl group, may also be substituted by a hydroxyl group or a C1-12 alkyl group or an alkoxy group, or interrupted by an oxygen atom, a carbonyl group, or an ester group independently or simultaneously.
[0081] In the chemical formula 1, R1 may be a functional group selected from a substituted or unsubstituted C1-20 alkyl group, a substituted or unsubstituted C1-30 acetal group, and a substituted or unsubstituted C1-30 hemiacetal group, R2 and R3 may each independently be hydrogen, and R4 and R5 may each independently or simultaneously be a functional group selected from hydrogen, a substituted or unsubstituted C6-18 aryl group, a substituted or unsubstituted C7-18 alkylaryl group, and a substituted or unsubstituted C7-18 aralkyl group. The functional group of R1, i.e., the alkyl group, may also be substituted by a hydroxyl group or a C1-12 alkyl group or an alkoxy group, or interrupted by an oxygen atom, a carbonyl group, or an ester group. In addition, R4 and R5 may more preferably each independently or simultaneously be a substituted or unsubstituted C6-18 aryl group.
[0082] In the chemical formula 1, R1 may be a substituted or unsubstituted C1-20 alkyl group, and R2 to R5 may each independently or simultaneously be a functional group selected from hydrogen and a substituted or unsubstituted C1-20 alkyl group.
[0083] The cured film obtained by using the photosensitive resin composition containing the UV absorber having such a definition has excellent sensitivity, resolution, transmittance, and light discoloration resistance, and not only no cracks are observed, but also the reliability of OLED can be improved. In addition, when using the photosensitive resin composition, due to its excellent solubility, precipitation and white turbidity do not occur, thereby improving the coating property.
[0084] Specifically, for conventional positive photosensitive compositions, compositions composed of an alkali-soluble resin and a 1,2-quinonediazide compound are thermally decomposed during hard baking after exposure and development. As a result, the transmittance in the visible light region is reduced, or when the cured film is exposed to heat above a certain temperature or absorbs high-energy short-wavelength light such as ultraviolet rays, some components of the cured film are decomposed to cause discoloration or impurities, thereby causing reliability problems in organic EL elements.
[0085] Furthermore, benzotriazole compounds are generally used as UV absorbers in conventional photosensitive compositions, but there are limitations in preventing discoloration of the cured film and there are problems such as resolution and white turbidity.
[0086] Therefore, the present invention uses a substance having a triazine skeleton of Chemical Formula 1 and specifically including one or more phenolic hydroxyl groups and alkoxy groups as functional groups as a UV absorber, thereby preventing the discoloration problem of the cured film and providing excellent light resistance and good heat resistance effects.
[0087] In addition, the UV absorber of the present invention has a higher molar absorption coefficient than the commonly used benzotriazole compounds, so when the same content is used, the UV absorption characteristics are enhanced. In addition, the UV absorber of the chemical formula 3 has an alkoxy functional group together with one or more phenolic hydroxyl groups, and a cross-linking reaction will be carried out when the compound having an alkoxy group such as a siloxane resin is heated. Through this cross-linking reaction, it can be stably present when further heated or the cured film is stored for a long time and exposed to visible light. In addition, the UV absorber exhibits good heat resistance.
[0088] The UV absorber may be included in an amount of 0.1 to 10 parts by weight or 5 to 10 parts by weight relative to 100 parts by weight of the siloxane copolymer. If the content of the UV absorber is less than 0.1 parts by weight, the light resistance is insufficient, and if the content is greater than 10 parts by weight, the sensitivity decreases, and there is a problem that it is difficult to realize a pattern.
[0089] The UV absorber and the 1,2-quinonediazide compound may be contained in a weight ratio of 1:1 to 1:20. If the content ratio is exceeded, problems of insufficient light resistance or decreased sensitivity may also occur, so their contents may be adjusted in an appropriate ratio.
[0090] In addition, the UV absorber may have an absorption range of 400 nm or less or 280 nm to 380 nm. Specifically, when the UV absorber is included in an amount of 0.1 to 10 parts by weight relative to the photosensitive resin, the UV absorber may have an absorption range of 400 nm or less or 280 nm to 380 nm.
[0091] Examples of these UV absorbers may be any one or more selected from the compounds represented by the following Chemical Formulae 4 to 5, Chemical Formula 6-1, Chemical Formula 6-2, Chemical Formulae 7 to 12, but the types thereof are not limited as long as they fall within the definition of Chemical Formula 1.
[0092] [Chemical formula 4]
[0093]
[0094] The chemical formula 4 is a structure in which R1 is a propyl group, R2, R3 and R4 are each independently a buthoxy group, and R5 is a hydroxyl group in the chemical formula 1, and has a maximum absorption wavelength at 350 nm.
[0095] [Chemical formula 5]
[0096]
[0097] The chemical formula 5 is a structure in which R1 is 4-[3-(2-ethylhexyl-1-oxy)-2-hydroxypropyl], R2, R3, R4 and R5 are each independently a methyl group in the chemical formula 1, and has a maximum absorption wavelength at 295 nm.
[0098] [Chemical formula 6]
[0099]
[0100] The chemical formula 6 is a structure in which R1 of the chemical formula 1 includes 4-[2-hydroxy-3-tridecyloxypropyl] and 4-[2-hydroxy-3-dodecyloxypropyl], R2, R3, R4 and R5 are each independently a methyl group, and has a maximum absorption wavelength at 295 nm.
[0101] That is, the chemical formula 6 represents a mixture of the following chemical formulas 6-1 and 6-2. The mixing ratio of the mixture of these chemical formulas 6-1 and 6-2 is not particularly limited, and can be, for example, a weight ratio of 1:99 to 99:1.
[0102] [Chemical formula 6-1]
[0103]
[0104] [Chemical formula 6-2]
[0105]
[0106] [Chemical formula 7]
[0107]
[0108] The chemical formula 7 is a structure in which R1 in the chemical formula 1 is isooctylpropanoate, R2 and R3 are each independently hydrogen, and R4 and R5 are each independently phenyl, and has a maximum absorption wavelength at 322 nm.
[0109] [Chemical formula 8]
[0110]
[0111] The chemical formula 8 is a structure in which R1 in the chemical formula 1 is an octyl group, and R2, R3, R4, and R5 are each independently a methyl group, and has a maximum absorption wavelength at 287 nm.
[0112] [Chemical formula 9]
[0113]
[0114] The chemical formula 9 is a structure in which R1 in the chemical formula 1 is 2-(2-ethylhexanoyloxy)ethyl, R2, R3, R4 and R5 are each independently hydrogen, and has a maximum absorption wavelength at 287 nm.
[0115] [Chemical formula 10]
[0116]
[0117] The chemical formula 10 is a structure in which R1 is 2-ethylhexyl, R2 is hydrogen, R3 is methoxy, R4 is 2-ethylhexyloxy, and R5 is hydroxyl in the chemical formula 1, and has a maximum absorption wavelength at 340 nm.
[0118] [Chemical formula 11]
[0119]
[0120] The chemical formula 11 is a structure in which R1 in the chemical formula 1 is 2-ethylhexyl, R2 and R3 are each independently hydrogen, and R4 and R5 are each independently phenyl, and has a maximum absorption wavelength at 370 nm.
[0121] [Chemical formula 12]
[0122]
[0123] The chemical formula 12 is a structure in which R1 in the chemical formula 1 is methyl, and R2, R3, R4, and R5 are each independently hydrogen, and has a maximum absorption wavelength at 290 nm.
[0124] The UV absorber may be a mixture of two kinds of materials, for example, i) a mixture selected from Chemical Formula 4, Chemical Formula 5, Chemical Formula 6-1 and Chemical Formula 6-2 and one selected from Chemical Formula 8; and ii) a mixture selected from Chemical Formula 7, Chemical Formula 9 and Chemical Formula 10.
[0125] As another example, the UV absorber may use a mixture of iii) one selected from Chemical Formula 9 and Chemical Formula 10; and iv) one selected from Chemical Formula 11 and Chemical Formula 12.
[0126] In addition, when the two UV absorbers are used, the mixing ratio of i) and ii) or iii) and iv) may be 25 to 75:75 to 25 by weight based on the total amount of the UV absorbers used.
[0127] d) Solvent
[0128] In the positive photosensitive resin composition of the present invention, the solvent may account for 10 to 90% by weight of the solid content of the entire resin composition. Therefore, the solvent content may be appropriately adjusted to satisfy the solid content range.
[0129] The solvent d) mentioned above can be one or more selected from methanol, ethanol, benzyl alcohol, hexanol, ethylene glycol methyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol methyl ether propionate, ethylene glycol ethyl ether propionate, ethylene glycol methyl ether, ethylene glycol ethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol methyl ethyl ether, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, propylene glycol methyl ether propionate, propylene glycol ethyl ether propionate, propylene glycol propyl ether propionate, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol propyl ether, propylene glycol butyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, butylene glycol monomethyl ether, butylene glycol monoethyl ether, dibutylene glycol dimethyl ether and dibutylene glycol diethyl ether.
[0130] e) Other additives
[0131] The positive photosensitive resin composition according to the present invention may further contain a surfactant to improve coating properties within a range that does not impair the effects of the present invention. Examples of such surfactants include fluorine-based surfactants, silicone-based surfactants, nonionic surfactants, and other surfactants.
[0132] In addition, in order to improve the chemical resistance and film adhesion of the composition according to the present invention, additives such as silane coupling agents that crosslink with hydroxyl groups or promote crosslinking, crosslinking agents, crosslinking accelerators, sensitizers, thermal free radical generators, thermal acid or thermal base generators, photoacid or photobase generators, dissolution accelerators, dissolution inhibitors, stabilizers, defoaming agents, etc. may be contained as needed within the range that does not impair the effects of the present invention.
[0133] Furthermore, the content of these surfactants and additives is not particularly limited and can be used according to methods known in the art.
[0134] Therefore, for example, the positive photosensitive resin composition of the present invention contains a) a siloxane copolymer, b) a 1,2-quinonediazide compound, (c) a UV absorber and (d) a solvent, and may further contain one or more of a surfactant and other additives to improve coating properties.
[0135] In the present invention, after mixing the above-mentioned components, the solution of the positive photosensitive resin composition is preferably filtered using a filter membrane with a pore size of about 0.1 μm before use.
[0136] When a cured film is formed using the photosensitive resin composition of the present invention, a cured film having a transmittance of 80% or more and less than 95% at 400 nm based on a film thickness of 3 μm can be formed.
[0137] Pattern forming method for display element and display element using the same
[0138] On the other hand, according to another embodiment of the present invention, a cured film is provided, which includes a cured product of the positive photosensitive resin composition.
[0139] Furthermore, the present invention provides a display element including a cured product of the positive photosensitive resin composition.
[0140] In this case, according to the present invention, a method for forming a display element pattern using the positive photosensitive resin composition can also be provided.
[0141] The OLED display includes a pixel defining layer (PDL) layer that divides the boundaries between self-luminous red, green, and blue pixels and insulates them, and an interlayer insulating film having both insulating properties and electrode flatness properties under the PDL layer. At this time, the PDL layer is precisely patterned by a photoetching process, so a photosensitive resin composition containing a polyamic acid compound has been widely used as a material for forming the PDL layer.
[0142] Therefore, in the present invention, a cured film including a cured product of the above-mentioned specific component positive photosensitive resin composition can be formed, and various display elements including such a cured film pattern can be provided.
[0143] Specifically, the positive photosensitive resin composition is coated on a semiconductor substrate to a certain thickness, and is pre-dried in a vacuum chamber and then pre-baked using a hot plate or an oven, so as to form a cured film including a cured product of the resin composition.
[0144] The semiconductor substrate includes, for example, a silicon substrate, a silicon nitride substrate, a substrate coated with metals such as aluminum, molybdenum, chromium, etc., a glass substrate, a quartz substrate, an ITO substrate, etc. The coating method may be spin coating, slit coating, slit coating followed by spin coating, spray coating, etc.
[0145] The heat treatment conditions are, for example, an optimal heating temperature and a heating time selected from the range of 70° C. to 150° C. and 0.5 minute to 30 minutes.
[0146] In addition, the thickness of the cured film formed from the positive photosensitive resin composition is, for example, 0.1 μm to 20 μm. The transmittance of the cured film at a wavelength of 400 nm and a film thickness of 3 μm may be 80% or more and less than 95%.
[0147] The cured film of the present invention is formed from a photosensitive resin composition containing a UV absorber, and has a transmittance of less than 95% at a short wavelength of 400 nm, which can prevent the problem of damage to materials such as elements when the transmittance is too high.
[0148] In addition, the present invention can form a pattern that can be applied to a display element using the cured film. That is, the present invention provides a method for forming a display element pattern using the positive photosensitive resin composition.
[0149] When the positive photosensitive cured film formed by the positive photosensitive resin composition of the present invention is exposed to ultraviolet light, ArF, KrF or the like using a mask having a predetermined pattern, the 1,2-quinonediazide derivative contained in the positive photosensitive resin film is carboxylated, and the exposed portion is soluble in an alkaline developer.
[0150] Then, when the exposed portion is developed with an alkaline developer, the exposed portion of the cured film formed of the positive photosensitive resin is removed, and a pattern is formed in accordance with the mask shape.
[0151] In addition, as for the developing method, the dipping method and the shaking dipping method can be used as the developing method. In this case, the developing time is usually 20 seconds to 180 seconds.
[0152] The positive photosensitive resin cured film after the alkali development is rinsed with running water, for example, for 20 to 120 seconds, and then dried by compressed air or compressed nitrogen or by a spin method, so that a film with moisture removed from the substrate and a pattern formed can be obtained.
[0153] Next, the pattern-forming film is post-baked to be thermally cured. Specifically, by heating with a hot plate or an oven, a cured film having excellent heat resistance, planarization performance, low absorption, etc. and having a good pattern formed thereon can be obtained.
[0154] The post-baking method generally includes treating the material at a heating temperature selected within the range of 130° C. to 300° C. for 5 to 30 minutes when using a hot plate, or for 20 to 90 minutes when using an oven.
[0155] As described above, the cured film formed by the positive photosensitive resin composition of the present invention not only has excellent performance such as resolution and flatness, but also has excellent weather resistance, which can ensure excellent panel reliability, and can thus be appropriately used as an interlayer insulating film, planarizing film or PDL in various OLED displays.
[0156] In other words, the positive photosensitive resin composition can be used to form an interlayer insulating film suitable for TFT-LCD, an interlayer insulating film of OLED, or an interlayer insulating film of O-TFT; a passivation insulating film of TFT-LCD, a passivation insulating film of OLED, or a passivation insulating film of O-TFT; a gate insulating film of TFT-LCD, a gate insulating film of OLED, or a gate insulating film of O-TFT; a flattening film of TFT-LCD, a flattening film of OLED, or a flattening film of O-TFT; or a pattern of a pixel define layer of OLED. The display element having a cured film forming these patterns shows excellent insulation and heat resistance that can maintain a stable shape up to about 350°C, can improve the defective rate against moisture, and can also provide excellent light resistance and weather resistance. In addition, the reliability of the display element can be improved.
[0157] The following examples are provided to help understand the present invention. However, the following examples are only used to illustrate the present invention, and the present invention is not limited to the following examples.
[0158] <Examples and Comparative Examples>
[0159] Silane copolymers were synthesized using the reactive silane monomers shown in Table 1 below. The molecular weights of the synthesized silane copolymers are shown in Table 2. Each synthesis example is described in detail below.
[0160]
Table 1
[0161]
[0162] Note: In Table 1, PTMS: phenyltrimethoxysilane DPDMS: diphenyldimethoxysilane DMDMS: dimethyldimethoxysilane GPTMS: 3-glycidoxypropyltrimethoxysilane ECETMS: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane MTMS: methyltrimethoxysilane PrTMS: propyltrimethoxysilane TMOS: tetramethoxysilane TEOS: tetraethoxysilane
[0163]
Table 2
[0164] synthesis Copolymer Mw(g / mol) 1 1-a 6,500 2 2-a 12,000 3 3-a 13,500 4 4-a 8,300 5 5-a 5,500 6 6-a 3,100 7 7-a 17,500 8 8-a 7,800 9 9-a 4,800 10 10-a 11,000 11 11-a 3,500 12 12-a 9,200 13 13-a 22,000 14 14-a 19,000 15 15-a 25,000 16 16-a 18,900 17 17-a 5,400 18 18-a 8,700 Comparative synthesis 1 20-a 1,900 Comparative synthesis 2 21-a 980 Comparative synthesis 3 22-a 38,000 Comparative synthesis 4 23-a 8,800 Comparative synthesis 5 24-a 31,000 Comparative Synthesis 6 1-b 6,800 Comparative Synthesis 7 6-b 2,900 Comparative synthesis 8 8-b 7,600 Comparative Synthesis 9 11-b 3,800 Comparative synthesis 10 12-b 9,700
[0165] <Examples and Comparative Examples>
[0166] [Synthesis Example 1]: Preparation of siloxane copolymer (1-a)
[0167] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 30 parts by weight of phenyltrimethoxysilane, 30 parts by weight of propyltrimethoxysilane, and 40 parts by weight of tetramethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was increased by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, it was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA (propylene glycol methyl ether acetate) were added for reduced pressure distillation to prepare a siloxane copolymer (1-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 6,500 (g / mol). Here, the weight average molecular weight is a weight average molecular weight in terms of polystyrene measured using GPC, and the weight average molecular weight is measured using a standard analysis method of a gel permeation chromatography (GPC) system, which is e2695 Alliance Separation Module manufactured by Waters.
[0168] [Synthesis Example 2]: Preparation of siloxane copolymer (2-a)
[0169] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 20 parts by weight of diphenyldimethoxysilane, 40 parts by weight of methyltrimethoxysilane, and 40 parts by weight of tetraethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% ammonia solution was dripped, and then the temperature was increased by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (2-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 12,000 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0170] [Synthesis Example 3]: Preparation of siloxane copolymer (3-a)
[0171] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 30 parts by weight of dimethyldimethoxysilane, 40 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 30 parts by weight of tetramethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (3-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 13,500 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0172] [Synthesis Example 4]: Preparation of siloxane copolymer (4-a)
[0173] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 35 parts by weight of dimethyldimethoxysilane, 35 parts by weight of methyltrimethoxysilane, and 30 parts by weight of tetramethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% ammonia solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (4-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 8,300 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0174] [Synthesis Example 5]: Preparation of siloxane copolymer (5-a)
[0175] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 30 parts by weight of diphenyldimethoxysilane, 30 parts by weight of propyltrimethoxysilane, and 40 parts by weight of tetramethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (5-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 5,500 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0176] [Synthesis Example 6]: Preparation of siloxane copolymer (6-a)
[0177] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 50 parts by weight of phenyltrimethoxysilane, 40 parts by weight of dimethyldimethoxysilane, and 10 parts by weight of tetraethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (6-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 3,100 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0178] [Synthesis Example 7]: Preparation of siloxane copolymer (7-a)
[0179] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 25 parts by weight of phenyltrimethoxysilane, 25 parts by weight of 3-glycidoxypropyltrimethoxysilane, and 50 parts by weight of tetramethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was increased by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (7-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 17,500 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0180] [Synthesis Example 8]: Preparation of siloxane copolymer (8-a)
[0181] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 30 parts by weight of diphenyldimethoxysilane, 10 parts by weight of dimethyldimethoxysilane, 20 parts by weight of propyltrimethoxysilane, and 40 parts by weight of tetraethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% ammonia solution was dripped, and then the temperature was increased by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (8-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 7,800 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0182] [Synthesis Example 9]: Preparation of siloxane copolymer (9-a)
[0183] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 70 parts by weight of dimethyldimethoxysilane, 10 parts by weight of methyltrimethoxysilane, and 20 parts by weight of tetraethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (9-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 4,800 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0184] [Synthesis Example 10]: Preparation of Siloxane Copolymer (10-a)
[0185] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 20 parts by weight of phenyltrimethoxysilane, 40 parts by weight of dimethyldimethoxysilane, and 40 parts by weight of tetramethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (10-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 11,000 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0186] [Synthesis Example 11]: Preparation of Siloxane Copolymer (11-a)
[0187] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 30 parts by weight of diphenyldimethoxysilane, 30 parts by weight of 3-glycidoxypropyltrimethoxysilane, and 40 parts by weight of tetrapropoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was increased by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (11-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 3,500 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0188] [Synthesis Example 12]: Preparation of Siloxane Copolymer (12-a)
[0189] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 40 parts by weight of diphenyldimethoxysilane, 45 parts by weight of methyltrimethoxysilane, and 15 parts by weight of tetramethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% ammonia solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (12-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 9,200 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0190] [Synthesis Example 13]: Preparation of Siloxane Copolymer (13-a)
[0191] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 35 parts by weight of phenyltrimethoxysilane, 15 parts by weight of methyltrimethoxysilane, and 50 parts by weight of tetraethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was increased by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (13-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 22,000 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0192] [Synthesis Example 14]: Preparation of Siloxane Copolymer (14-a)
[0193] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 40 parts by weight of diphenyldimethoxysilane, 15 parts by weight of propyltrimethoxysilane, and 45 parts by weight of tetramethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was increased by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (14-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 19,000 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0194] [Synthesis Example 15]: Preparation of Siloxane Copolymer (15-a)
[0195] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 40 parts by weight of phenyltrimethoxysilane, 10 parts by weight of propyltrimethoxysilane, and 50 parts by weight of tetraethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was increased by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (15-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 25,000 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0196] [Synthesis Example 16]: Preparation of Siloxane Copolymer (16-a)
[0197] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 25 parts by weight of diphenyldimethoxysilane, 35 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 40 parts by weight of tetraethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% ammonia solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (16-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 18,900 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0198] [Synthesis Example 17]: Preparation of Siloxane Copolymer (17-a)
[0199] In a 2L three-necked flask with a thermometer, a condenser and a stirrer, 80 parts by weight of diphenyldimethoxysilane and 20 parts by weight of tetramethoxysilane were added as reactive silanes, and stirred slowly at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% ammonia solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (17-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 5,400 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0200] [Synthesis Example 18]: Preparation of Siloxane Copolymer (18-a)
[0201] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 60 parts by weight of phenyltrimethoxysilane and 40 parts by weight of tetraethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (18-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 8,700 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0202] [Synthesis Example 19]: Preparation of 1,2-quinonediazide compound (A)
[0203] 1 mol of a phenol compound represented by the following Chemical Formula G and 2 mol of 1,2-naphthoquinonediazide-5-sulfonic acid chloride were reacted to prepare a 1,2-naphthoquinonediazide-5-sulfonic acid ester compound having an esterification degree of 67%.
[0204] [Chemical formula G]
[0205]
[0206] [Comparative Synthesis Example 1]: Preparation of Siloxane Copolymer (20-a)
[0207] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 95 parts by weight of phenyltrimethoxysilane and 5 parts by weight of tetraethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% ammonia solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (20-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 1,900 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0208] [Comparative Synthesis Example 2]: Preparation of Siloxane Copolymer (21-a)
[0209] In a 2L three-necked flask with a thermometer, a condenser and a stirrer, 95 parts by weight of methyltrimethoxysilane and 5 parts by weight of tetramethoxysilane were added as reactive silanes, and stirred slowly at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% aqueous acetic acid solution was dripped, and then the temperature was increased by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (21-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 980 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0210] [Comparative Synthesis Example 3]: Preparation of Siloxane Copolymer (22-a)
[0211] In a 2L three-necked flask with a thermometer, a condenser and a stirrer, 93 parts by weight of 3-glycidoxypropyltrimethoxysilane and 7 parts by weight of tetrapropoxysilane were added as reactive silanes, and stirred slowly at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was increased by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (22-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 38,000 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0212] [Comparative Synthesis Example 4]: Preparation of Siloxane Copolymer (23-a)
[0213] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 4 parts by weight of diphenyldimethoxysilane, 4 parts by weight of dimethyldimethoxysilane, and 92 parts by weight of tetramethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (23-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 8,800 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0214] [Comparative Synthesis Example 5]: Preparation of Siloxane Copolymer (24-a)
[0215] In a 2L three-necked flask with a thermometer, a condenser, and a stirrer, 5 parts by weight of diphenyldimethoxysilane, 4 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 91 parts by weight of tetramethoxysilane were added as reactive silanes, and slowly stirred at room temperature for 1 hour in a nitrogen environment. After the reaction solution was cooled to 10°C, 30 parts by weight of a 5% acetic acid aqueous solution was dripped, and then the temperature was raised by 5°C per minute until 60°C and maintained for 12 hours. After polycondensation, the reaction was cooled to room temperature to terminate the reaction. Then, the catalyst and unreacted monomers were removed by water washing and extraction processes, and 30 parts by weight of PGMEA were added for vacuum distillation to prepare a siloxane copolymer (24-a) with a solid content of 40%. The weight average molecular weight of the siloxane copolymer is 31,000 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight converted to polystyrene measured using GPC.
[0216] [Reference Synthesis Example 1]: Preparation of Siloxane Copolymer (1-b)
[0217] The same method was used except for the process of removing the catalyst and unreacted monomers by washing and extraction in Synthesis Example 1. At this time, the weight average molecular weight is the weight average molecular weight of polystyrene conversion measured by GPC, and its value is 6,800 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight of polystyrene conversion measured by GPC.
[0218] [Reference Synthesis Example 2]: Preparation of Siloxane Copolymer (6-b)
[0219] The same method was used except for the process of removing the catalyst and unreacted monomers by washing and extraction in Synthesis Example 6. At this time, the weight average molecular weight is the weight average molecular weight of polystyrene conversion measured by GPC, and its value is 2,900 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight of polystyrene conversion measured by GPC.
[0220] [Reference Synthesis Example 3]: Preparation of Siloxane Copolymer (8-b)
[0221] The same method was used except for the process of removing the catalyst and unreacted monomers by washing and extraction in Synthesis Example 8. At this time, the weight average molecular weight is the weight average molecular weight of polystyrene conversion measured by GPC, and its value is 7,600 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight of polystyrene conversion measured by GPC.
[0222] [Reference Synthesis Example 4]: Preparation of Siloxane Copolymer (11-b)
[0223] The same method was used except for the process of removing the catalyst and unreacted monomers by water washing and extraction process in Synthesis Example 11. At this time, the weight average molecular weight is the weight average molecular weight of polystyrene conversion measured by GPC, and its value is 3,800 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight of polystyrene conversion measured by GPC.
[0224] [Reference Synthesis Example 5]: Preparation of Siloxane Copolymer (12-b)
[0225] The same method was used except for the process of removing the catalyst and unreacted monomers by washing and extraction in Synthesis Example 12. At this time, the weight average molecular weight is the weight average molecular weight of polystyrene conversion measured by GPC, and its value is 9,700 (g / mol). At this time, the weight average molecular weight is the weight average molecular weight of polystyrene conversion measured by GPC.
[0226] [UV absorber]
[0227] The UV absorbers used in the following Examples, Comparative Examples, and Reference Examples are as follows.
[0228] [Chemical formula 4]
[0229]
[0230] The chemical formula 4 is a structure in which R1 is a propyl group, R2, R3 and R4 are each independently a buthoxy group, and R5 is a hydroxyl group in the chemical formula 1, and has a maximum absorption wavelength at 350 nm.
[0231] [Chemical formula 5]
[0232]
[0233] The chemical formula 5 is a structure in which R1 in the chemical formula 1 is 4-[3-(2-ethylhexyl-1-oxy)-2-hydroxypropyl, R2, R3, R4 and R5 are each independently a methyl group, and has a maximum absorption wavelength at 295 nm.
[0234] [Chemical formula 6]
[0235]
[0236] The chemical formula 6 is a structure in which R1 of the chemical formula 1 includes 4-[2-hydroxy-3-tridecyloxypropyl] and 4-[2-hydroxy-3-dodecyloxypropyl], R2, R3, R4 and R5 are each independently a methyl group, and has a maximum absorption wavelength at 295 nm.
[0237] The chemical formula 6 represents a mixture of the following chemical formulas 6-1 and 6-2. TINUVIN400 (product name) equivalent to the chemical formula 6 is used in the following examples, comparative examples, and reference examples.
[0238] [Chemical formula 6-1]
[0239]
[0240] [Chemical formula 6-2]
[0241]
[0242] [Chemical formula 7]
[0243]
[0244] The chemical formula 7 is a structure in which R1 in the chemical formula 1 is isooctylpropanoate, R2 and R3 are each independently hydrogen, and R4 and R5 are each independently phenyl, and has a maximum absorption wavelength at 322 nm.
[0245] [Chemical formula 8]
[0246]
[0247] The chemical formula 8 is a structure in which R1 in the chemical formula 1 is an octyl group, and R2, R3, R4, and R5 are each independently a methyl group, and has a maximum absorption wavelength at 287 nm.
[0248] [Chemical formula 9]
[0249]
[0250] The chemical formula 9 is a structure in which R1 in the chemical formula 1 is 2-(2-ethylhexanoyloxy)ethyl, R2, R3, R4 and R5 are each independently hydrogen, and has a maximum absorption wavelength at 287 nm.
[0251] [Chemical formula 10]
[0252]
[0253] The chemical formula 10 is a structure in which R1 is 2-ethylhexyl, R2 is hydrogen, R3 is methoxy, R4 is 2-ethylhexyloxy, and R5 is hydroxyl in the chemical formula 1, and has a maximum absorption wavelength at 340 nm.
[0254] [Chemical formula 11]
[0255]
[0256] The chemical formula 11 is a structure in which R1 in the chemical formula 1 is 2-ethylhexyl, R2 and R3 are each independently hydrogen, and R4 and R5 are each independently phenyl, and has a maximum absorption wavelength at 370 nm.
[0257] [Chemical formula 12]
[0258]
[0259] The chemical formula 12 is a structure in which R1 in the chemical formula 1 is methyl, and R2, R3, R4, and R5 are each independently hydrogen, and has a maximum absorption wavelength at 290 nm.
[0260] [Chemical formula 13]
[0261]
[0262] The structure is CAS No. 116244-12-3, Uvinul (registered trademark) T150, and has a maximum absorption wavelength at 310 nm.
[0263] [Chemical formula 14]
[0264]
[0265] The structure is CAS No. 31274-51-8, Tris-biphenyl triazine (TBPT), and has a maximum absorption wavelength at 305 nm.
[0266] [Chemical formula 15]
[0267]
[0268] The structure is CAS No. 127519-17-9, TINUVIN (registered trademark) 384-2, and has a maximum absorption wavelength at 345 nm.
[0269] [Chemical formula 16]
[0270]
[0271] The structure is CAS No. 102577-46-8, TINUVIN (registered trademark) 1130, and has a maximum absorption wavelength at 348 nm.
[0272] [Chemical formula 17]
[0273]
[0274] The structure is CAS No. 70321-86-7, TINUVIN (registered trademark) 900, and has a maximum absorption wavelength at 348 nm.
[0275] Preparation of positive photosensitive resin composition
[0276] [Example 1]
[0277] Relative to 100 parts by weight of the siloxane copolymer (1-a) prepared in the synthesis example 1, 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in the synthesis example 19 and 8 parts by weight of the UV absorber of [chemical formula 4] are mixed, and propylene glycol methyl ether acetate is used to dissolve the mixture until the solid content reaches 30 parts by weight, and then the mixture is filtered with a 0.1 μm microporous filter membrane to prepare a positive photosensitive resin composition.
[0278] [Example 2]
[0279] A photosensitive resin composition was prepared by the same method as in Example 1, except that the UV absorber of [Chemical Formula 5] was used instead of the UV absorber of [Chemical Formula 4] in Example 1.
[0280] [Example 3]
[0281] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (2-a) of Synthesis Example 2 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 6] was used instead of [Chemical Formula 4].
[0282] [Example 4]
[0283] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (2-a) of Synthesis Example 2 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 8] was used instead of [Chemical Formula 4].
[0284] [Example 5]
[0285] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (3-a) of Synthesis Example 3 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 10] was used instead of [Chemical Formula 4].
[0286] [Example 6]
[0287] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (3-a) of Synthesis Example 3 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 12] was used instead of [Chemical Formula 4].
[0288] [Example 7]
[0289] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (4-a) of Synthesis Example 4 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 9] was used instead of [Chemical Formula 4].
[0290] [Example 8]
[0291] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (4-a) of Synthesis Example 4 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 11] was used instead of [Chemical Formula 4].
[0292] [Example 9]
[0293] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (5-a) of Synthesis Example 5 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 7] was used instead of [Chemical Formula 4].
[0294] [Example 10]
[0295] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (5-a) of Synthesis Example 5 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1.
[0296] [Example 11]
[0297] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (6-a) of Synthesis Example 6 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 5] was used instead of [Chemical Formula 4].
[0298] [Example 12]
[0299] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (6-a) of Synthesis Example 6 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 6] was used instead of [Chemical Formula 4].
[0300] [Example 13]
[0301] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (7-a) of Synthesis Example 7 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 8] was used instead of [Chemical Formula 4].
[0302] [Example 14]
[0303] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (7-a) of Synthesis Example 7 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 10] was used instead of [Chemical Formula 4].
[0304] [Example 15]
[0305] A photosensitive siloxane resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (8-a) of Synthesis Example 8 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1 and [Chemical Formula 12] was used instead of [Chemical Formula 4].
[0306] [Example 16]
[0307] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (8-a) of Synthesis Example 8 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 9] was used instead of [Chemical Formula 4].
[0308] [Example 17]
[0309] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (9-a) of Synthesis Example 9 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 11] was used instead of [Chemical Formula 4].
[0310] [Example 18]
[0311] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (9-a) of Synthesis Example 9 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 7] was used instead of [Chemical Formula 4].
[0312] [Example 19]
[0313] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (10-a) of Synthesis Example 10 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1.
[0314] [Example 20]
[0315] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (10-a) of Synthesis Example 10 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 5] was used instead of [Chemical Formula 4].
[0316] [Example 21]
[0317] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (11-a) of Synthesis Example 11 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 6] was used instead of [Chemical Formula 4].
[0318] [Example 22]
[0319] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (11-a) of Synthesis Example 11 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 6] was used instead of [Chemical Formula 4].
[0320] [Example 23]
[0321] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (12-a) of Synthesis Example 12 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 10] was used instead of [Chemical Formula 4].
[0322] [Example 24]
[0323] A photosensitive siloxane resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (12-a) of Synthesis Example 12 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1 and [Chemical Formula 12] was used instead of [Chemical Formula 4].
[0324] [Example 25]
[0325] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (13-a) of Synthesis Example 13 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 9] was used instead of [Chemical Formula 4].
[0326] [Example 26]
[0327] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (13-a) of Synthesis Example 13 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 11] was used instead of [Chemical Formula 4].
[0328] [Example 27]
[0329] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (14-a) of Synthesis Example 14 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 7] was used instead of [Chemical Formula 4].
[0330] [Example 28]
[0331] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (14-a) of Synthesis Example 14 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1.
[0332] [Example 29]
[0333] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (15-a) of Synthesis Example 15 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 5] was used instead of [Chemical Formula 4].
[0334] [Example 30]
[0335] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (15-a) of Synthesis Example 15 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 6] was used instead of [Chemical Formula 4].
[0336] [Example 31]
[0337] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (16-a) of Synthesis Example 16 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 8] was used instead of [Chemical Formula 4].
[0338] [Example 32]
[0339] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (16-a) of Synthesis Example 16 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 10] was used instead of [Chemical Formula 4].
[0340] [Example 33]
[0341] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (17-a) of Synthesis Example 17 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 12] was used instead of [Chemical Formula 4].
[0342] [Example 34]
[0343] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (17-a) of Synthesis Example 17 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 9] was used instead of [Chemical Formula 4].
[0344] [Example 35]
[0345] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (18-a) of Synthesis Example 18 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 11] was used instead of [Chemical Formula 4].
[0346] [Example 36]
[0347] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (18-a) of Synthesis Example 18 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 7] was used instead of [Chemical Formula 4].
[0348] [Example 37]
[0349] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (2-a) of Synthesis Example 2 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1, and 4 parts by weight of [Chemical Formula 6] and 4 parts by weight of [Chemical Formula 12] were used instead of 8 parts by weight of [Chemical Formula 4].
[0350] [Example 38]
[0351] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (2-a) of Synthesis Example 2 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1, and 4 parts by weight of [Chemical Formula 8] and 4 parts by weight of [Chemical Formula 9] were used instead of 8 parts by weight of [Chemical Formula 4].
[0352] [Example 39]
[0353] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (3-a) of Synthesis Example 3 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1, and 6 parts by weight of [Chemical Formula 10] and 2 parts by weight of [Chemical Formula 12] were used instead of 8 parts by weight of [Chemical Formula 4].
[0354] [Example 40]
[0355] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (3-a) of Synthesis Example 3 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1, and 6 parts by weight of [Chemical Formula 9] and 2 parts by weight of [Chemical Formula 11] were used instead of 8 parts by weight of [Chemical Formula 4].
[0356] [Example 41]
[0357] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (4-a) of Synthesis Example 4 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1, and 2 parts by weight of [Chemical Formula 4] and 6 parts by weight of [Chemical Formula 7] were used instead of 8 parts by weight of [Chemical Formula 4].
[0358] [Example 42]
[0359] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (4-a) of Synthesis Example 4 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1, and 6 parts by weight of [Chemical Formula 5] and 2 parts by weight of [Chemical Formula 10] were mixed and used instead of 8 parts by weight of [Chemical Formula 4].
[0360] [Example 43]
[0361] A photosensitive resin composition was prepared by the same method as in Example 1, except that 0.5 parts by weight of [Chemical Formula 4] was used instead of 8 parts by weight of [Chemical Formula 4] in Example 1.
[0362] [Example 44]
[0363] A photosensitive resin composition was prepared by the same method as in Example 1, except that 8 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 8 parts by weight of [Chemical Formula 12] was used instead of 8 parts by weight of [Chemical Formula 4].
[0364] [Example 45]
[0365] A photosensitive resin composition was prepared by the same method as in Example 1, except that 8 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 0.5 parts by weight of [Chemical Formula 8] was used instead of 8 parts by weight of [Chemical Formula 4].
[0366] [Example 46]
[0367] A photosensitive resin composition was prepared by the same method as in Example 1, except that 48 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 8 parts by weight of [Chemical Formula 9] was used instead of 8 parts by weight of [Chemical Formula 4].
[0368] [Example 47]
[0369] A photosensitive resin composition was prepared by the same method as in Example 1, except that 48 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 0.5 parts by weight of [Chemical Formula 6] was used instead of 8 parts by weight of [Chemical Formula 4].
[0370] [Comparative Example]
[0371] 1) Preparation of siloxane copolymer without using the UV absorber of the present application
[0372] In order to compare the physical properties when the UV absorber in the present invention is not used, photosensitive resin compositions of Comparative Examples 1 to 11 were prepared.
[0373] [Comparative Example 1]
[0374] A photosensitive resin composition was prepared by the same method as in Example 1, except that [Chemical Formula 13] was used instead of [Chemical Formula 4] in Example 1.
[0375] [Comparative Example 2]
[0376] A photosensitive resin composition was prepared by the same method as in Example 1, except that [Chemical Formula 14] was used instead of [Chemical Formula 4] in Example 1.
[0377] [Comparative Example 3]
[0378] A photosensitive resin composition was prepared by the same method as in Example 1, except that [Chemical Formula 16] was used instead of [Chemical Formula 4] in Example 1.
[0379] [Comparative Example 4]
[0380] A photosensitive resin composition was prepared by the same method as in Example 1, except that [Chemical Formula 17] was used instead of [Chemical Formula 4] in Example 1.
[0381] [Comparative Example 5]
[0382] A photosensitive resin composition was prepared by the same method as in Example 1, except that [Chemical Formula 15] was used instead of [Chemical Formula 4] in Example 1.
[0383] [Comparative Example 6]
[0384] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (5-a) of Synthesis Example 5 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 13] was used instead of [Chemical Formula 4].
[0385] [Comparative Example 7]
[0386] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (5-a) of Synthesis Example 5 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 14] was used instead of [Chemical Formula 4].
[0387] [Comparative Example 8]
[0388] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (5-a) of Synthesis Example 5 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 16] was used instead of [Chemical Formula 4].
[0389] [Comparative Example 9]
[0390] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (5-a) of Synthesis Example 5 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 17] was used instead of [Chemical Formula 4].
[0391] [Comparative Example 10]
[0392] A photosensitive resin composition was prepared by the same method as in Example 1 except that the siloxane copolymer (5-a) of Synthesis Example 5 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 and [Chemical Formula 15] was used instead of [Chemical Formula 4].
[0393] [Comparative Example 11]
[0394] A photosensitive resin composition was prepared by the same method as in Example 1, except that no UV absorber was used.
[0395] 2) Preparation of siloxane copolymers with changed quinonediazide content or UV absorber type
[0396] In order to compare the physical properties when the content of quinonediazide is different from that of Example 1 of the present application and when the UV absorber of the present application is not used or a UV absorber of a different type from that of the present application is mixed, photosensitive resin compositions of Comparative Examples 12 to 18 were prepared.
[0397] [Comparative Example 12]
[0398] A photosensitive resin composition was prepared by the same method as in Example 1, except that 54 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 and no UV absorber was used.
[0399] [Comparative Example 13]
[0400] A photosensitive resin composition was prepared by the same method as in Example 1, except that 3 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1 and no UV absorber was used.
[0401] [Comparative Example 14]
[0402] A photosensitive resin composition was prepared by the same method as in Example 1, except that 54 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 4 parts by weight and 4 parts by weight of [Chemical Formula 13] were used instead of 8 parts by weight of the UV absorber of [Chemical Formula 4].
[0403] [Comparative Example 15]
[0404] A photosensitive resin composition was prepared by the same method as in Example 1, except that 54 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 4 parts by weight of [Chemical Formula 5] and 4 parts by weight of [Chemical Formula 14] were used instead of 8 parts by weight of the UV absorber of [Chemical Formula 4].
[0405] [Comparative Example 16]
[0406] A photosensitive resin composition was prepared by the same method as in Example 1, except that 54 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 9 parts by weight of [Chemical Formula 10] and 1 part by weight of [Chemical Formula 15] were used instead of 8 parts by weight of the UV absorber of [Chemical Formula 4].
[0407] [Comparative Example 17]
[0408] A photosensitive resin composition was prepared by the same method as in Example 1, except that 54 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 9 parts by weight of [Chemical Formula 6] and 1 part by weight of [Chemical Formula 17] were used instead of 8 parts by weight of the UV absorber of [Chemical Formula 4].
[0409] [Comparative Example 18]
[0410] A photosensitive resin composition was prepared by the same method as in Example 1, except that 54 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 9 parts by weight and 1 part by weight of [Chemical Formula 16] were used instead of 8 parts by weight of the UV absorber of [Chemical Formula 4].
[0411] [Reference example]
[0412] 1) Preparation of siloxane copolymer modified siloxane copolymer
[0413] In order to compare the physical properties of Comparative Synthesis Examples 1 to 10 prepared by changing the reactive silane monomer instead of the siloxane copolymer of Synthesis Example 1 used in the present application, photosensitive resin compositions of Reference Examples 1 to 10 were prepared.
[0414] [Reference Example 1]
[0415] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (20-a) of Comparative Synthesis Example 1 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1.
[0416] [Reference Example 2]
[0417] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (21-a) of Comparative Synthesis Example 2 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1 and 8 parts by weight of [Chemical Formula 6] was used instead of 8 parts by weight of [Chemical Formula 4].
[0418] [Reference Example 3]
[0419] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (22-a) of Comparative Synthesis Example 3 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1 and 8 parts by weight of [Chemical Formula 10] was used instead of 8 parts by weight of [Chemical Formula 4].
[0420] [Reference Example 4]
[0421] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (23-a) of Comparative Synthesis Example 4 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1 and 8 parts by weight of [Chemical Formula 9] was used instead of 8 parts by weight of [Chemical Formula 4].
[0422] [Reference Example 5]
[0423] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (24-a) of Comparative Synthesis Example 5 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1 and 8 parts by weight of [Chemical Formula 7] was used instead of 8 parts by weight of [Chemical Formula 4].
[0424] [Reference Example 6]
[0425] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (1-b) of Reference Synthesis Example 1 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1 and 8 parts by weight of [Chemical Formula 11] was used instead of 8 parts by weight of [Chemical Formula 4].
[0426] [Reference Example 7]
[0427] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (6-b) of Reference Synthesis Example 2 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1 and 8 parts by weight of [Chemical Formula 12] was used instead of 8 parts by weight of [Chemical Formula 4].
[0428] [Reference Example 8]
[0429] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (8-b) of Reference Synthesis Example 3 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1 and 8 parts by weight of [Chemical Formula 8] was used instead of 8 parts by weight of [Chemical Formula 4].
[0430] [Reference Example 9]
[0431] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (11-b) of Reference Synthesis Example 4 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1 and 8 parts by weight of [Chemical Formula 5] was used instead of 8 parts by weight of [Chemical Formula 4].
[0432] [Reference Example 10]
[0433] A photosensitive resin composition was prepared by the same method as in Example 1, except that the siloxane copolymer (12-b) of Reference Synthesis Example 5 was used instead of the siloxane copolymer (1-a) of Synthesis Example 1 in Example 1, and 4 parts by weight of [Chemical Formula 4] and 4 parts by weight of [Chemical Formula 10] were used instead of 8 parts by weight of [Chemical Formula 4].
[0434] 2) Preparation of siloxane copolymers with varying contents of quinonediazide and / or UV absorber
[0435] In order to compare the physical properties when the content of quinonediazide and / or UV absorber is different from that of Example 1 of the present application and exceeds the scope of the present application, photosensitive resin compositions of Reference Examples 11 to 18 were prepared.
[0436] [Reference Example 11]
[0437] A photosensitive resin composition was prepared by the same method as in Example 1, except that 54 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1 and 8 parts by weight of [Chemical Formula 6] was used as a UV absorber.
[0438] [Reference Example 12]
[0439] A photosensitive resin composition was prepared by the same method as in Example 1, except that 54 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 12 parts by weight of [Chemical Formula 7] was used instead of 8 parts by weight of the UV absorber of [Chemical Formula 4].
[0440] [Reference Example 13]
[0441] A photosensitive resin composition was prepared by the same method as in Example 1, except that 8 parts by weight of the UV absorber of [Chemical Formula 4] in Example 1 was replaced with 12 parts by weight of [Chemical Formula 6].
[0442] [Reference Example 14]
[0443] A photosensitive resin composition was prepared by the same method as in Example 1, except that 3 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 8 parts by weight of [Chemical Formula 10] was used instead of 8 parts by weight of the UV absorber of [Chemical Formula 4].
[0444] [Reference Example 15]
[0445] A photosensitive resin composition was prepared by the same method as in Example 1, except that 3 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 12 parts by weight of [Chemical Formula 12] was used instead of 8 parts by weight of the UV absorber of [Chemical Formula 4].
[0446] [Reference Example 16]
[0447] A photosensitive resin composition was prepared by the same method as in Example 1, except that 8 parts by weight of the UV absorber of [Chemical Formula 4] in Example 1 was replaced with 12 parts by weight of [Chemical Formula 9].
[0448] [Reference Example 17]
[0449] A photosensitive resin composition was prepared by the same method as in Example 1, except that 8 parts by weight of the UV absorber of [Chemical Formula 4] in Example 1 was replaced with 12 parts by weight of [Chemical Formula 7].
[0450] [Reference Example 18]
[0451] A photosensitive resin composition was prepared by the same method as in Example 1, except that 3 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 was used instead of 23 parts by weight of the 1,2-naphthoquinonediazide compound (A) prepared in Synthesis Example 19 in Example 1, and 6 parts by weight and 6 parts by weight of [Chemical Formula 11] were used instead of 8 parts by weight of the UV absorber of [Chemical Formula 4].
[0452] [Experimental example]
[0453] The sensitivity, resolution, transmittance, resistance to light discoloration, cracking, precipitation, white turbidity, and OLED reliability of the above-mentioned examples, reference examples, and comparative examples were measured and are shown in Tables 1 and 2 below.
[0454] a) Sensitivity
[0455] The film formed as above was irradiated with a predetermined pattern mask at a 15 μm line and space (line & space) 1:1 CD standard dose (Dose) at an intensity of 20 mW / cm at 435 nm. 2 The film was then developed with a 2.38 wt % tetramethylammonium hydroxide aqueous solution at 23° C. for 1 minute, and then rinsed with ultrapure water for 1 minute.
[0456] Then, the film was cured in an oven at 250° C. for 60 minutes to obtain a pattern-cured film having a thickness of 3 μm.
[0457] b) Resolution
[0458] The minimum dimension of the pattern normally formed in the pattern cured film formed when measuring the sensitivity in a) above was measured. A minimum dimension less than 3 μm was indicated as ○, 3 μm to less than 5 μm was indicated as △, and 5 μm or more was indicated as ×.
[0459] c) Transmittance and light discoloration resistance
[0460] For the evaluation of transmittance and light discoloration resistance, the 400nm transmittance of the patterned cured film formed when measuring the sensitivity in a) above was measured using a spectrophotometer. In addition, in order to measure the light discoloration resistance, the transmittance change rate was measured after irradiating with 500J of energy using a metal halide lamp. When the transmittance change rate is greater than or equal to 10%, it is indicated as ×, when it is from 5% to less than 10%, it is indicated as △, and when it is less than 5%, it is indicated as ○.
[0461] d) Crack
[0462] For evaluation of cracks, the transmittance evaluation substrate was visually inspected and observed under a microscope at 100 times magnification, and the case where cracks were observed was indicated as ×, the case where cracks were observed only at the coating edge was indicated as △, and the case where no cracks were observed was indicated as ○.
[0463] e) Precipitation
[0464] For the evaluation of precipitation, the prepared positive photosensitive resin composition was coated on a glass substrate with a spin coater, and then pre-baked on a hot plate at 110°C for 2 minutes to form a film with a thickness of 3.2 μm. The film was visually inspected and observed under a microscope at 100 times to observe whether precipitation caused by insufficient solubility occurred. When no precipitation occurred, it was indicated as ○, and when precipitation occurred, it was indicated as ×.
[0465] f) White turbidity
[0466] For the evaluation of white turbidity, the prepared positive photosensitive resin composition was coated on a glass substrate with a spin coater, and then pre-baked on a hot plate at 110°C for 2 minutes to form a film with a thickness of 3.2 μm. The film was measured with a haze meter, and 0 to less than 0.5 was represented by ○, 0.5 to less than 1 was represented by △, and greater than or equal to 1 was represented by ×.
[0467] g) OLED reliability
[0468] The sensitivity was determined by the same method as in a) above. Figure 1A pattern film is formed on the patterned ITO substrate shown, and EL is deposited. Al (aluminum) is deposited on the upper part using a cathode electrode for encapsulation process. The time (T97) when the brightness drops by 3% when the element is turned on (On) is evaluated at 85°C and 85% RH. The situation of ensuring more than 1000 hours is indicated as ○, and the situation of less than 1000 hours is indicated as ×.
[0469] <Experimental Example 1>
[0470] Physical property comparison based on UV absorber type
[0471] Physical properties of Examples 1 to 36 were compared with Comparative Examples 1 to 12 which did not use the UV absorber of the present application. The results are shown in Tables 3, 4 and 5, respectively.
[0472]
Table 3
[0473]
[0474]
Table 4
[0475]
[0476]
Table 5
[0477]
[0478] As can be seen from Tables 3, 4 and 5 above, the positive photosensitive resin compositions prepared in Examples 1 to 36 according to the present invention, as compared with Comparative Examples 1 to 11, not only have excellent overall performance such as sensitivity and resolution, but also have excellent weather resistance, i.e., light discoloration resistance, thereby ensuring excellent panel reliability, and can be effectively applied to interlayer insulating films, planarizing films or PDLs, etc. in various OLED displays, due to the use of the specific UV absorber of Chemical Formula 1 together with the siloxane copolymer and the quinonediazide compound.
[0479] In contrast, since Comparative Examples 1 to 10 contain benzotriazole or benzotriazine UV absorbers of a type different from that of the present application, even if any one of the physical properties such as sensitivity, transmittance, light discoloration resistance, cracks, and white turbidity is excellent, the other physical properties are poor, thereby reducing the reliability of OLED. In addition, Comparative Example 11 does not use the UV absorber according to the present invention together, so the light discoloration resistance and OLED reliability are reduced.
[0480] <Experimental Example 2>
[0481] Comparison of physical properties based on siloxane copolymer types
[0482] The physical properties of Example 1 and Comparative Examples 12 to 18 in which the content of quinonediazide exceeded the range of the present application, or the UV absorber of the present application was not used, or a UV absorber of a different type from that of the present application was mixed were compared. The results are shown in Table 6.
[0483]
Table 6
[0484]
[0485] As can be seen from Table 6 above, compared with Example 1 of the present invention, Comparative Examples 12 and 13 have poor resolution because the content of quinone diazide exceeds the scope of the present application, and in particular, because no UV absorber is used, the light discoloration resistance is also poor, and the overall panel reliability is poor. In addition, Comparative Examples 14 to 18 also use the absorber of the present application, but contain benzotriazole or benzotriazine UV absorbers of different types from the present application, and the content of quinone diazide compounds is relatively excessive. Therefore, even if any one of the physical properties such as sensitivity, transmittance, light discoloration resistance, cracks and white turbidity is excellent, the other physical properties are also poor, thereby reducing the reliability of OLED.
[0486] <Experimental Example 3>
[0487] Comparison of physical properties based on siloxane copolymer types
[0488] The physical properties of Example 1 and Reference Examples 1 to 10 using different siloxane copolymers were compared. The results are shown in Table 7.
[0489]
Table 7
[0490]
[0491] It can be seen from Table 7 above that when different types of siloxane copolymers are included compared to Example 1, even if the UV absorber is the same as that in the present application, some of the physical properties such as sensitivity, transmittance, resistance to light discoloration, cracks and white turbidity will be insufficient. This shows that when a siloxane copolymer with a specific structure is used, the properties can be further improved.
[0492] <Experimental Example 4>
[0493] Comparison of physical properties based on siloxane copolymer types
[0494] The physical properties of Example 1 and Reference Examples 11 to 18 in which the contents of quinonediazide and / or UV absorber were outside the range of the present application were compared. The results are shown in Table 8.
[0495]
Table 8
[0496]
[0497] As can be seen from Table 8, Reference Examples 11 and 12 have poor resolution and reduced OLED reliability due to excessive quinonediazide compound content compared to Example 1. In particular, Reference Example 12 has a white turbidity phenomenon due to excessive UV absorber content.
[0498] In addition, Reference Examples 13 to 18 also failed to satisfy the physical properties such as sensitivity, transmittance, resistance to light discoloration, cracking, and white turbidity because the content of the quinonediazide compound was too small or the content of the UV absorber was too large.
[0499] <Experimental Example 5>
[0500] Physical property comparison based on UV absorber content ratio
[0501] In order to compare the physical properties based on the content ratio of quinonediazide and UV absorber, physical property evaluation was performed according to the composition shown in the following table. The results are shown in Table 9.
[0502]
Table 9
[0503]
[0504] As can be seen from Table 9 above, there is a tendency that the sensitivity is slightly reduced or the light discoloration resistance effect is reduced depending on the content ratio of the UV absorber and the quinonediazide compound.
Claims
1. A positive photosensitive resin composition, comprising: a) 100 parts by weight of siloxane copolymer; b) 5 to 50 parts by weight of a 1,2-quinonediazide compound; c) 0.1 to 10 parts by weight of one or more UV absorbers represented by the following Chemical Formula 1; and d) a solvent, wherein the content of the solvent is 10 to 90% by weight of the solid content of the entire resin composition, The siloxane-based copolymer comprises a copolymer having an unreacted monomer content of less than 10% by weight and a residual catalyst content of less than 2,000 ppm, [Chemical formula 1] In the chemical formula 1, R1 is selected from hydrogen, substituted or unsubstituted C1-20 alkyl, substituted or unsubstituted C3-20 cycloalkyl, substituted or unsubstituted C2-10 alkenyl, substituted or unsubstituted C6-18 aryl, substituted or unsubstituted C7-18 alkaryl, substituted or unsubstituted C7-18 aralkyl, substituted or unsubstituted C1-20 alkoxy, substituted or unsubstituted C1-30 acetal, substituted or unsubstituted C1-30 hemiacetal, substituted or unsubstituted a substituted C1-20 heteroalkyl group, a substituted or unsubstituted C3-20 heterocycloalkyl group, a substituted or unsubstituted C2-10 heteroalkenyl group, a substituted or unsubstituted C6-18 heteroaryl group, a substituted or unsubstituted C7-18 heteroalkylaryl group, a substituted or unsubstituted C7-18 heteroaralkyl group, a substituted or unsubstituted C1-20 heteroalkoxy group, a substituted or unsubstituted C1-30 heteroacetal group, and a substituted or unsubstituted C1-30 heterohemiacetal group, R2 to R5 are each independently the same or different and are selected from hydrogen, hydroxy, substituted or unsubstituted C1-20 alkyl, substituted or unsubstituted C3-20 cycloalkyl, substituted or unsubstituted C2-10 alkenyl, substituted or unsubstituted C6-18 aryl, substituted or unsubstituted C7-18 alkaryl, substituted or unsubstituted C7-18 aralkyl, substituted or unsubstituted C1-20 alkoxy, substituted or unsubstituted C1-30 acetal, substituted or unsubstituted C1-30 The functional group is a hemiacetal group, a substituted or unsubstituted C1-20 heteroalkyl group, a substituted or unsubstituted C3-20 heterocycloalkyl group, a substituted or unsubstituted C2-10 heteroalkenyl group, a substituted or unsubstituted C6-18 heteroaryl group, a substituted or unsubstituted C7-18 heteroalkylaryl group, a substituted or unsubstituted C7-18 heteroaralkyl group, a substituted or unsubstituted C1-20 heteroalkoxy group, a substituted or unsubstituted C1-30 heteroacetal group and a substituted or unsubstituted C1-30 heterohemiacetal group.
2. The positive photosensitive resin composition according to claim 1, wherein In the chemical formula 1, R1 is a substituted or unsubstituted C1-20 alkyl group, R2 to R4 are each independently or simultaneously a functional group selected from hydrogen and a substituted or unsubstituted C1-20 alkoxy group, and R5 is a hydroxyl group.
3. The positive photosensitive resin composition according to claim 1, wherein In the chemical formula 1, R1 is a functional group selected from a substituted or unsubstituted C1-20 alkyl group, a substituted or unsubstituted C1-30 acetal group, and a substituted or unsubstituted C1-30 hemiacetal group, and R2 to R5 are each independently or simultaneously a substituted or unsubstituted C1-20 alkyl group.
4. The positive photosensitive resin composition according to claim 3, wherein The functional groups of R1, i.e., the alkyl groups, are each independently or simultaneously substituted by a hydroxyl group or a C1-12 alkyl group or alkoxy group, or are interrupted by an oxygen atom, a carbonyl group, or an ester group.
5. The positive photosensitive resin composition according to claim 1, wherein In the chemical formula 1, R1 is a functional group selected from a substituted or unsubstituted C1-20 alkyl group, a substituted or unsubstituted C1-30 acetal group and a substituted or unsubstituted C1-30 hemiacetal group, R2 and R3 are each independently hydrogen, and R4 and R5 are each independently or simultaneously a functional group selected from hydrogen, a substituted or unsubstituted C6-18 aryl group, a substituted or unsubstituted C7-18 alkylaryl group and a substituted or unsubstituted C7-18 aralkyl group.
6. The positive photosensitive resin composition according to claim 5, wherein The functional groups of R1, i.e., the alkyl groups, are each independently or simultaneously substituted by a hydroxyl group or a C1-12 alkyl group or alkoxy group, or are interrupted by an oxygen atom, a carbonyl group, or an ester group.
7. The positive photosensitive resin composition according to claim 1, wherein In the chemical formula 1, R1 is a substituted or unsubstituted C1-20 alkyl group, and R2 to R5 are each independently or simultaneously a functional group selected from hydrogen and a substituted or unsubstituted C1-20 alkyl group.
8. The positive photosensitive resin composition according to claim 1, wherein The siloxane copolymer is obtained by hydrolyzing and polycondensing i) 10 to 90 parts by weight of a silane compound represented by the following Chemical Formula 2 and ii) 10 to 90 parts by weight of a silane compound represented by the following Chemical Formula 3 relative to 100 parts by weight of the total monomers. [Chemical formula 2] <h2 style=";text-align:left;direction:ltr">(R6)<h2 style=";text-align:left;direction:ltr"> n <h2 style=";text-align:left;direction:ltr"> Si(R7)<h2 style=";text-align:left;direction:ltr"> 4-n In the chemical formula 2, R6 may be the same or different from each other and is selected from a hydrogen atom, a C1-10 alkyl group, a C2-10 acyl group, a C2-10 alkenyl group or a C6-20 aryl group, R7 may be the same or different from each other and is selected from a hydrogen atom, an alkoxy group or a chloro group, n is an integer from 1 to 3, [Chemical formula 3] Si(OR8)4 In the chemical formula 3, R8 are each independently the same or different and are selected from methyl, ethyl, propyl, isopropyl or butyl.
9. The positive photosensitive resin composition according to claim 1, wherein The siloxane copolymer has a weight average molecular weight of 1,000 g / mol to 30,000 g / mol in terms of polystyrene.
10. The positive photosensitive resin composition according to claim 1, wherein The 1,2-quinonediazide compound is one or more selected from 1,2-quinonediazide-4-sulfonate, 1,2-quinonediazide-5-sulfonate and 1,2-quinonediazide-6-sulfonate.
11. The positive photosensitive resin composition according to claim 1, wherein The UV absorber is any one or more selected from the compounds represented by the following Chemical Formulae 4 to 5, Chemical Formula 6-1, Chemical Formula 6-2, and Chemical Formulae 7 to 12, [Chemical formula 4] [Chemical formula 5] [Chemical formula 6-1] [Chemical formula 6-2] [Chemical formula 7] [Chemical formula 8] [Chemical formula 9] [Chemical formula 10] [Chemical formula 11] [Chemical formula 12] 12. The positive photosensitive resin composition according to claim 11, wherein The UV absorber is a mixture of two comprising the following mixtures: i) a mixture selected from Chemical Formula 4, Chemical Formula 5, Chemical Formula 6-1 and Chemical Formula 6-2 and one of Chemical Formula 8; and ii) a mixture selected from Chemical Formula 7, Chemical Formula 9 and Chemical Formula 10; or iii) one selected from Chemical Formula 9 and Chemical Formula 10; and iv) a mixture of one selected from Chemical Formula 11 and Chemical Formula 12.
13. The positive photosensitive resin composition according to claim 1, wherein The solvent d) is one or more selected from methanol, ethanol, benzyl alcohol, hexanol, ethylene glycol methyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol methyl ether propionate, ethylene glycol ethyl ether propionate, ethylene glycol methyl ether, ethylene glycol ethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol methyl ethyl ether, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, propylene glycol methyl ether propionate, propylene glycol ethyl ether propionate, propylene glycol propyl ether propionate, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol propyl ether, propylene glycol butyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, butylene glycol monomethyl ether, butylene glycol monoethyl ether, dibutylene glycol dimethyl ether and dibutylene glycol diethyl ether.
14. The positive photosensitive resin composition according to claim 1, wherein The UV absorber and the 1,2-quinonediazide compound are included in a weight ratio of 1:1 to 1:
20. 15 . A cured film comprising a cured product of the positive photosensitive resin composition according to claim 1 . 16 . The cured film according to claim 15 , which has a transmittance of 80% or more and less than 95% at a wavelength of 400 nm and a film thickness of 3 μm. 17 . A display element comprising a cured product of the positive photosensitive resin composition according to claim 1 .
Citation Information
Patent Citations
Content-based gaussian noise reduction for still image, video and film
CA2610262A1
Positioning bracket
CA2640265A1
Device for reducing a drag produced by the relative displacement of a body and fluid
CA2670268A1
Precursors for plasma activated conformal film deposition
KR1020190126256A
Blue photosensitive resin composition, color filter produced by using same, and image display device
CN110121679A